Foot and Ankle Hepatocellular Carcinoma Metastasis. (January 2016) - Parashar, Kalind; Pandit-Taskar, Neeta
Abstract : Abstract: Bone is the third most common site of metastasis from hepatocellular carcinoma (HCC), the first two being the lung and lymph nodes, respectively. Metastatic HCC has been reported in the vertebrae, ribs, pelvis, and femur, which are more common sites of bone metastases. We present a case of HCC with metastasis to the distal tibia, fibula, and small bones of the feet as the only sites of bone metastasis, along with a brief literature review.